Change in Blood Pressure Variability Among Treated Elderly Hypertensive Patients and Its Association With Mortality - Chowdhury, Enayet; Nelson, M.R.; Wing, L.M.H.; Jennings, G.L.R.; Beilin, L.J.; Reid, Christopher; Bruce, A.; Beckinsale, P.; Thompson, J.; McMurchie, M.; Fraser, G.; Gleave, D.; et al. (WILEY, 2019)
Background: Information is scarce regarding effects of antihypertensive medication on blood pressure variability (BPV) and associated clinical outcomes. We examined whether antihypertensive treatment changes BPV over time and whether such change (decline or increase) has any association with long-term mortality in an elderly hypertensive population. Methods and Results: We used data from a subset of participants in the Second Australian National Blood Pressure study (n=496) aged ≥65 years who had 24-hour ambulatory blood pressure recordings at study entry (baseline) and then after a median of 2 years while on treatment (follow-up). Weighted day-night systolic BPV was calculated for both baseline and follow-up as a weighted mean of daytime and nighttime blood pressure standard deviations. The annual rate of change in BPV over time was calculated from these BPV estimates. Furthermore, we classified both BPV estimates as high and low based on the baseline median BPV value and then classified BPV changes into stable: low BPV, stable: high BPV, decline: high to low, and increase: low to high. We observed an annual decline (mean±SD: −0.37±1.95; 95% CI, −0.54 to −0.19; P<0.001) in weighted day-night systolic BPV between baseline and follow-up. Having constant stable: high BPV was associated with an increase in all-cause mortality (hazard ratio: 3.03; 95% CI, 1.67–5.52) and cardiovascular mortality (hazard ratio: 3.70; 95% CI, 1.62–8.47) in relation to the stable: low BPV group over a median 8.6 years after the follow-up ambulatory blood pressure monitoring. Similarly, higher risk was observed in the decline: high to low group. Conclusions: Our results demonstrate that in elderly hypertensive patients, average BPV declined over 2 years of follow-up after initiation of antihypertensive therapy, and having higher BPV (regardless of any change) was associated with increased long-term mortality.